Challenges and opportunities for ELSI early career researchers. Issue 1 (December 2016) - Bell, Jessica; Ancillotti, Mirko; Coathup, Victoria; Coy, Sarah; Rigter, Tessel; Tatum, Travis; Grewal, Jasjote; Akcesme, Faruk; Brkić, Jovana; Causevic-Ramosevac, Anida; Milovanovic, Goran; Nobile, Marianna; et al.
Abstract Background Over the past 25 years, there has been growing recognition of the importance of studying the Ethical, Legal and Social Implications (ELSI) of genetic and genomic research. A large investment into ELSI research from the National Institutes of Health (NIH) Human Genomic Project budget in 1990 stimulated the growth of this emerging field; ELSI research has continued to develop and is starting to emerge as a field in its own right. The evolving subject matter of ELSI research continues to raise new research questions as well as prompt re-evaluation of earlier work and a growing number of scholars working in this area now identify themselves as ELSI scholars rather than with a particular discipline. Main text Due to the international and interdisciplinary nature of ELSI research, scholars can often find themselves isolated from disciplinary or regionally situated support structures. We conducted a workshop with Early Career Researchers (ECRs) in Oxford, UK, and this paper discusses some of the particular challenges that were highlighted. While ELSI ECRs may face many of the universal challenges faced by ECRs, we argue that a number of challenges are either unique or exacerbated in the case of ELSI ECRs and discuss some of the reasons as to why this may be the case. We identify some of the most pressing issues for ELSI ECRs as: interdisciplinary angst and expertise, isolation from traditional support structures, limited resources and funding opportunities, and uncertainty regarding how research contributions will be measured. We discuss the potential opportunity to use web 2.0 technologies to transform academic support structures and address some of the challenges faced by ELSI ECRs, by helping to facilitate mentoring and support, access to resources and new accreditation metrics. Conclusion As our field develops it is crucial for the ELSI community to continue looking forward to identify how emerging digital solutions can be used to facilitate the international and interdisciplinary research we perform, and to offer support for those embarking on, progressing through, and transitioning into an ELSI research career.